PENERAPAN SISTEM INFORMASI MANAJEMEN PT. GAS ALAM SEJAHTERA SIDOARJO - Radinal Rizki Styanto (AKUNTANSI 45, 2022)
The research objective was to determine the role of Management Information Systems at PT. Prosperous Natural Gas Sidoarjo. The research method uses a qualitative approach with informants from the management of PT. Sejahteraa Natural Gas Sidoarjo. Data collection by observation and interviews. The results showed that there was no computer-based management information system at PT. Prosperous Natural Gas Sidoarjo. All records use manual records, making it very difficult for users to find just one data. Therefore PT. Gas Alam Sejahtera requires a Management Information System that has been computerized to facilitate company management in making decisions.